Experimentelles Prüfverfahren an einem Vierlagerprüfstand zur Ermitt-lung des Reibungsmomentes einer einzelnen Angular Roller Unit unter axialer und radialer Last - Wirsching, Sven; Hierold, Patrick; Stahl, Thomas; Tremmel, Stephan; Wartzack, Sandro (61. Tribologie-Fachtagung 2020 Reibung, Schmierung und Verschleiß Forschung und praktische Anwendungen, 2020)
Different types of rolling bearing arrangements are used in gearbox applications. The load carrying capacity and fric-tional power of the rolling bearings has a significant influence on the efficiency and performance of the gear unit. A precise knowledge of the load condition of the rolling bearings can be used to reduce friction, so that energy can be saved and the performance can be optimally used. The experimental determination of the frictional torque is an im-portant component for the further development and validation of new bearing geometries. The performance of the rolling bearing must be checked over the speed and load ranges. In many cases, the bearing arrangements are not under purely axial or radial load but under combined load. Initially, only purely axial or purely radial loads can be usefully investigated on conventional two or four bearing test rigs. For this purpose, the total frictional torque of both or all four bearings is measured. Due to the symmetrical distribution of the load to the bearings, it is possible to derive the frictional torque of the individual bearing. Therefore, the evaluation of the frictional torque of the single bearing on a four-bearing test rig would be a cost-effective alternative to a single bearing test rig. This procedure is not allowed for bearings under combined load, because in the present case the outer bearings receive a combination of axial and radial force and the middle bearings the radial force. For this reason, the following paper presents an experimental test method that allows the determination of the frictional torque of a single bearing on a four-bearing test rig. In the test, the total frictional torque of all two or four bearings is measured. The outer two bearings can be loaded axially and simultaneously radially. The middle bearings transmit the radial load. In order to determine the frictional torque for the outer bearings, first, tests are executed with four purely radially loaded ball bearings. In the next step, tests are performed with the testing bearings under purely radial load. In a further step, the rolling bearings are combined so that the testing bearings are inserted at the outer positions and the ball bearings at the middle once. By evaluating the total frictional moment in the tests, the frictional moments of the individual bearings can be calculated and an error estimation is possible. Finally, this bearing arrangement is tested under a combined load condition and the frictional torque of the testing bearings is determined under consideration of the error. The results of the tests are analyzed and discussed.<br
Keywords: rolling bearing; friction; combined load; four bearing test rig; experiment